'We are all in the same storm but not in the same boat': the COVID pandemic and the Further Education Sector. Issue 8 (17th November 2022) - Spours, Ken; Grainger, Paul; Vigurs, Carol
ABSTRACT: The quotation in the title from a college leader is a stark reflection of the experience of the Further Education (FE) Sector during the COVID pandemic (2020–21). Traditionally regarded as a poor relation of the English education system, evidence from Sector sources suggest that the five COVID harms identified through a scoping review of the latest research closely mirror the main social and educational features of English general FE colleges. The pandemic has led to longer-term harms on vocational learning, with major disruptions to college-based courses and to apprenticeships, a stagnation situation captured in the metaphor 'educational long-COVID'. The analysis conceptualises the impact of the pandemic on FE provision and learners as leading to a 'COVID learning and skills equilibrium'; whereas effective mitigations are conceptualised through the idea of 'COVID recovery ecosystems'. Rapid review evidence suggests that the most effective way of addressing system-wide disruption is the development of integrated, strategic actions at local and regional levels to address vocational learning losses, facilitate greater entry-to-employment and to create more job opportunities for young people. Without these longer-term measures it is likely that the negative effects of the pandemic on the FE Sector could become further entrenched.